Robot cognition and navigation an experiment with mobile robots - Patnaik, Srikanta. (Cognitive technologies,)
In this book the author employs a cybernetic view of robot cognition and perception as he examines mobile robot simulations, realizations and experiments, and explains the related mathematical models and algorithms. Chapters are dedicated to map building, path planning, navigation using genetic algorithms, and robot programming packages. Then detailed chapters examine the programs required for robot parameter display, gripper control, sonar reading display, teleoperation, autonomous navigation, image capture and 3D perception. This book will be useful for students and engineers building intelligent robots, and researchers migrating to this field. The required source code is included in the book or available online. Cybernetic view of robot cognition and perception -- Map building -- Path planning -- Navigation using a genetic algorithm -- Robot programming packages -- Robot parameter display -- Program for botspeak -- Gripper control program -- Program for sonar reading display -- Program for wandering within the workspace -- Program for tele-operation -- A complete program for autonomous navigation -- Imaging geometry -- Image capture program -- Building 3D perception using a Kalman filter -- Program for 3D perception -- Perceptions of non-planar surfaces -- intelligent Garbage collection.